A inserção feminina no mercado de trabalho militar brasileiro - Mota, Emily Santos (2020)
This research has as main problem the issue of female advancement in the military job market, and unfolds this analysis within the institutional economy, treating social thinking and habits as necessary bases to analyze in what context this advancement has occurred within the career. When entering into the discussion of gender as a social institution, forming habits and female stereotypes that contribute to the social division of labor in the market in question, the main objective of the research was to analyze how these women have progressed, and for that, used data provided by the Citizen Information System (e - SIC). The results were obtained through a descriptive analysis, and were tested in hypotheses formed based on readings of research related to the area and in periods prior to the one currently analyzed. The advance was characterized by the presence of women in the Armed Forces, by their rise, and the type of specialization that each one operates repeatedly. The final result mostly corroborated with the hypotheses in question, leading to the realization that women have indeed advanced in this market, remaining more present in all forces and gradually occupying positions previously held only by men, however, it is still done realize the difficulty of such an advance, the delay in re